Gender-inclusive language in the Faculty of Education of Bilbao: A preliminary analysis of its use in official languages - Idoiaga Mondragón, Nahia; Axpe Saex, Inge; Martín Etxebeste, Jon (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Gender-inclusive language, related to less sexist attitudes, it is not usual, even in educational contexts. This study analyzes the importance that university students, faculty, and Administrative and Service Staff gives to inclusive language in the Faculty of Education of Bilbao (UPV/EHU), and whether they value differently its use in Basque and Spanish. Participants (165) were 83% women, 16.4% men and 1 person of non-binary sex (0.6%). The average age was 27.76 years (SD = 11.87). The attitude towards inclusive language is positive and is recognized as a tool to reduce gender inequity, but its use is far from being common.